Beam transport system selection on the accelerator LU-10 - Dovbnya, A.N.; Guk, I.S.; Kononenko, S.G.; Tarasenko, A.S. (Вопросы атомной науки и техники, 2013)
Presently at the NSC KIPT the upgrading of the linear accelerator LU-10, designed for radiation processing of materials and products within the range of about 10 MeV, is started. For the accelerator operation time be used more efficiently it is supposed to design the second beam output onto the target. Possible variants of the second channel have been considered. The beam characteristics and beam losses are calculated with taking into account the desired parameters of the beam at the accelerating section output. Analysis of some channel variants by various criteria has been performed. The most effective version is chosen. У ННЦ ХФТІ розпочата модернізація лінійного прискорювача ЛП-10, що використовується для радіаційної обробки матеріалів і виробів у діапазоні до 10 МеВ. У зв'язку з цим для більш раціонального використання часу роботи прискорювача передбачається створення другого каналу виводу пучка на мішені. Розглянуто можливі варіанти створення каналу, розраховано характеристики пучка і втрати його з урахуванням передбачуваних параметрів пучка на виході прискорювальної секції. Проведено аналіз за різними критеріями й обраний найбільш ефективний варіант. В ННЦ ХФТИ в настоящее время начата модернизация линейного ускорителя ЛУ-10, используемого для радиационной обработки материалов и изделий в диапазоне до 10 МэВ. В связи с этим для более рационального использования времени работы ускорителя предполагается создание второго вывода пучка на мишени. Рассмотрены возможные варианты создания канала, рассчитаны характеристики пучка и потери его с учётом предполагаемых параметров пучка на выходе ускоряющей секции. Проведен анализ по различным критериям и выбран наиболее эффективный вариант.